Arrimos da memória dos imigrantes italianos e seus descendentes: alimentação, família, casa, objetos, terra natal e bairro (1942-1960) - Nascimento, Débora Cristina (2014)
This research sought, through oral testimonies, to document the support references and upholding elements used by both immigrants and their descendants established in São Paulo. This is a study of the dietary traditions brought from the maternal home of the Italian families of the past and present, such as the interviewees recalled them regarding the material culture, and the experiences in their native land and, subsequently, in the Brás neighborhood and the private space of their own homes. Based on reflections on orality and memory, since the sources used here consisted of testimonies and books of memoirs, we sought to understand the (re)significations often nostalgic and idyllic that these groups created on their past and their habits, as well as the subjectivity of their statements in the present moment, their silences and omissions. From the interviews conducted between the years 2010 to 2012, that prioritized Italians from different regions of Italy and their descendants, we were able to observe the regional differences in cuisine and customs, as well as the terrible experience of hunger, the hardship and the Italian history itself during World War II. As for the descendants, who reports what they learned from their elders, we perceived how this memory was reelaborated and what they incorporated from past generations with regard to values, dietary habits and heritage